2019
DOI: 10.3389/fimmu.2019.01729
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Function of Non-cell-bound CD73 in Inflammation

Abstract: Extracellular adenine nucleotides participate in cell-to-cell communication and modulate the immune response. The concerted action of ectonucleotidases CD39 and CD73 plays a major role in the local production of anti-inflammatory adenosine, but both ectonucleotidases are rarely co-expressed by human T cells. The expression of CD39 on T cells increases upon T cell activation and is high at sites of inflammation. CD73, in contrast, disappears from the cellular membrane after activation. The possibility that CD73… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 87 publications
1
55
0
Order By: Relevance
“…Despite their complementary function, CD39 and CD73 are rarely co-expressed on peripheral human lymphocytes (with the exception of B cells) [19]. In humans, CD73 is generally expressed on endothelial cells, B cells, naïve CD8 + T cells, and a subset of memory CD4 + T cells [20]. Recent studies show that upon activation, CD73 may be shed from the cell surface resulting in a disturbance of ATP/ADO balance in the extracellular matrix (ECM) [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite their complementary function, CD39 and CD73 are rarely co-expressed on peripheral human lymphocytes (with the exception of B cells) [19]. In humans, CD73 is generally expressed on endothelial cells, B cells, naïve CD8 + T cells, and a subset of memory CD4 + T cells [20]. Recent studies show that upon activation, CD73 may be shed from the cell surface resulting in a disturbance of ATP/ADO balance in the extracellular matrix (ECM) [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, CD73 is generally expressed on endothelial cells, B cells, naïve CD8 + T cells, and a subset of memory CD4 + T cells [20]. Recent studies show that upon activation, CD73 may be shed from the cell surface resulting in a disturbance of ATP/ADO balance in the extracellular matrix (ECM) [20,21]. In fact, cells that lose CD73 could be protected by pericellular ADO, thus maintaining their effector function [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on their Km values (PAP: 0.37–2 mM: CD73: 24 µM) using AMP as a substrate [ 61 , 62 , 63 ], a preponderant role of CD73 could be conjectured around the formation of adenosine over PAP. Further, it has been suggested that the conversion of AMP to adenosine may be produced by CD73 and, less efficiently, by alkaline phosphatase (PAP) [ 64 ]. However, the acidification of the tumor microenvironment caused by lactic acid which is secreted from cancer cells could lead to disturbances around the activity of the proteins in question [ 65 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results rule out any relevant CD39 activity in serum of patients with melanoma, according to previous reports showing that ATPase and ADPase activities in human blood are mainly mediated by cell-bound enzymes. 19 Expression of CD39 was also evaluated in serum samples from healthy subjects (n=10) and patients with melanoma (n=31). No difference was observed in CD39 expression between the two groups (online supplemental figure 2b).…”
Section: Baseline Cd73 Activity and Expression Are High In Serum Of Pmentioning
confidence: 99%